If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 6 = 7x + 34 Reorder the terms: 6 + 11x = 7x + 34 Reorder the terms: 6 + 11x = 34 + 7x Solving 6 + 11x = 34 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + 11x + -7x = 34 + 7x + -7x Combine like terms: 11x + -7x = 4x 6 + 4x = 34 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + 4x = 34 + 0 6 + 4x = 34 Add '-6' to each side of the equation. 6 + -6 + 4x = 34 + -6 Combine like terms: 6 + -6 = 0 0 + 4x = 34 + -6 4x = 34 + -6 Combine like terms: 34 + -6 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| 9x-26=73 | | 10.4+2.4b=-5.2 | | 7x-5=-5 | | 3g-63(g-8)=42 | | .6c+4=-9 | | 7a-6=12 | | 3+3p-5p+19=10p+130-3P | | 2x-1.8=4x-3.4 | | 13-2x=21 | | y+5=8-y | | 20+4m=2+2m | | x+3(x-2)=14 | | 2(3-4x)=-10 | | 6(a+3)=24 | | 2(y-1)=9 | | 3(x+4)=12 | | -78-10x=83-36x | | 7-8x=83-36x | | 3x+8=-100-9x | | 182-6x=6x+14 | | 71-2x=7x+17 | | 5x+6=87-4x | | 11x-16=8x+2 | | 5x+38=8x+14 | | 9x+7=3x+31 | | (7+x)=21 | | (g-2)=6 | | 4(3x+5)-6(3x-5)=12x+3(2x-6) | | 3h=90-h | | 7d=20 | | 2p-7=1 | | 14y-51=187+4y |